Essential requirements for connection of terminal equipment to 2-wire analogue interfaces, without capacitive termination, of public switched telecommunication networks using either the earth calling, the loop calling-disconnect clearing, the loop calling-guarded clearing or the loop calling-unguarded clearing signalling method. (15th September 1996) - British Standards Institution,
No abstract available